The Interplay Between Use of Biological Therapies, Psychological State, and the Microbiome in IBD - Tavakoli, Paris; Vollmer-Conna, Ute; Hadzi-Pavlovic, Dusan; Vázquez-Campos, Xabier; Grimm, Michael Carl (Frontiers in Medicine, 2022)
The interplay between use of biological therapies, psychological state, and the microbiome in IBD Background: Therapeutic aims in IBDs are to induce remission through rapidly effective treatment. Conventional therapeutic methods have been available for more than half a century with biological therapies the treatment of choice. There has been little attempt to longitudinally examine the differences in biopsychological factors and their associations with treatment modalities in IBD patients. Methods: 50 IBD participants (24 UC, 26 CD) in clinical remission were followed for 12 months. Complete longitudinal datasets were collected for analysis of association. Microbiome analysis was performed using V4 16SrRNA for identification of microbial phylogenetic relationships. Patients were grouped on whether or not they were in remission and on biological agents. Results: At the baseline, similar ecological indices were identified between the two treatment options in both disease classes; (Shannon, p = 0.380; Pielou’s, p = 0.246; Chao1, p = 0.934). At family level, CD group showed significant differences (Wilcoxon, p ≤ 0.05) between the treatment received (biologics vs non-biologic) in the abundance of Barnesiellaceae, Bifidobacteriaceae, unclassified Clostridia, and Clostridiaceae (Figure 1A). Results showed similar ecological index values in samples from the two treatment options. Samples in UC groups on biological and non-biologic treatment modes were found to have significantly different microbial communities based on Bray-Curtis dissimilarity (PERMANOVA, p = 0.0031). Microbial family composition in UC group and on two treatment modalities showed a total of 12 families that were significantly different (Wilcoxon, p ≤ 0.05): Acidaminococcaceae, unclassified Bacteroidales, Barnesiellaceae, Christensenellaceae, Clostridiales vadinBB60 group, Coriobacteriaceae, Defluvitaleaceae, Eggerthelaceaem Fusobacteriaceae, Muribaculaceae, Prevotellaceae, and Streptococcaceae (Figure1B). Results identified significant differences in microbial diversity (Shannon index, p = 0.041), and evenness (Pielou’s evenness, p = 0.045) between the two treatment modes. No differences were identified in richness (Chao1) in UC participants. Conclusion: Baseline biological indices were mostly similarly distributed between the two treatment options in remissive IBD patients, however biological therapy significantly influenced longitudinal trends of some microbiome dynamics, especially in UC. This suggests an underlying interrelationship between mode of treatment and biopsychological trajectories which might overshadow response to the treatment, requiring further assessment.